An intervention mapping approach to the development and evaluation of a community-based prostate cancer early detection programme in Nigeria. - Musliu Adetola Tolani; Christian Agbo Agbo; Shehu Salihu Umar; Alan Paciorek; Rufus Wale Ojewola; Faruk Mohammed; Mamoudou Maiga; Ernie Kaninjing; Muhammed Ahmed; Rebecca DeBoer (PLOS Global Public Health)
Interventions are needed to reduce the global disparity in prostate cancer outcomes. Our research aimed to evaluate the acceptability, feasibility and appropriateness of a stakeholder-developed intervention for the early detection of prostate cancer in Nigeria. This was a mixed methods study conducted at three cities in Nigeria. The intervention mapping framework was utilized as the primary framework for the study. During intervention development, a six-member team developed an implementation research logic model and then conducted stakeholder engagement to prioritize the preliminary intervention strategies among 12 purposively selected stakeholders. This was followed by brainstorming sessions by the same intervention development team for the selection of multi-faceted intervention strategies. Key informant interviews were then conducted among 10 purposively selected Nigerian clinicians, institutional leaders, and policymakers for contextual inquiry on the developed intervention. Descriptive statistics and qualitative analysis were performed. At the end of the intervention development process, the primary intervention strategies included supported risk assessment and patient navigation. The secondary strategies were education and training, and cancer information communication. The main actors of the intervention were trained community-based healthcare providers while the targeted population were adult men 40 years and above. The informants strongly noted that the intervention actions were feasible. Regarding acceptability, informants strongly believed that the intervention had numerous relative advantages but noted its complexity and the potential risk for overdiagnosis. Informants also consistently acknowledged that the intervention was appropriate but had mixed disposition on implementation preparedness. Further adaptations were made to address the stakeholder-identified gaps. In conclusion, this study developed a prostate cancer early detection intervention with preliminary feasibility, the first rigorously developed systems-strengthening intervention to optimize the detection of early-stage prostate cancer in Nigeria. A pilot implementation trial will be helpful in further testing the intervention in the field setting.